What is the effect of strength and conditioning training interventions on mechanical stiffness? A systematic review and meta-analysis - Bandara, U.; Coltman, C. E.; Portus, M.; Feros, S. A.; Talukdar, K.; Spratford, W. A. (Journal of Sports Sciences, 2025)
Mechanical stiffness, including vertical (Kvert), leg (Kleg), and joint (Kjoint) stiffness, is an important mechanical determinant associated with neuromuscular and athletic performances that influences force production and energy transformation. Strength and conditioning (S&C) coaches employ diverse training methods to improve athletes` mechanical stiffness. This systematic review and meta-analysis examined the effect of S&C interventions on mechanical stiffness. A comprehensive search across six electronic databases, including CINAHL, COCHRANE LIBRARY, MEDLINE, SCOPUS, SPORT DISCUSS, and WEB OF SCIENCE, identified 23 studies (40 intervention groups, 632 subjects) for the systematic review, with 12 studies (20 intervention groups, 420 subjects) included in the pre-post or/and control-intervention random effects meta-analysis. Plyometric or jump-related training had a significant and small effect on Kleg (SMD = 0.38; Z = 2.61, p = 0.009). When plyometrics training was combined with balance training, a significant and large effect on Kleg occurred (SMD = 0.80; Z = 2.93, p = 0.003). Resisted sprint training had a significant and large effect on Kleg (SMD = 0.80; Z = 6.07, p < 0.0001). These findings provide initial guidance for S&C coaches in designing programs to enhance mechanical stiffness. Future research directions are suggested to further explore the impact of S&C interventions on stiffness.